The Potential Impact on Trade of a Monetary Union in Southern Africa - Mbano, Sharon (Graduate School of Business (GSB), 2019)
Southern Africa has been exploring regional integration in the context of the Southern African Development Community (SADC). This dissertation seeks to examine the potential bilateral trade volume within SADC, that can be generated as a result of a hypothetical SADC currency union and to analyse its importance for policy. It can serve as a basis for the promotion of regional integration as a means of increasing intraregional trade in the region, on the continent and, ultimately, international trade. Regional monetary unions are envisaged by the African Union (AU) as building blocks towards an eventual continent-wide monetary union. In this respect a gravity model was estimated with panel data using pooled Ordinary Least Squares (OLS), random and fixed effect estimations covering the period 2000 to 2017. Because a SADC multilateral currency union does not exist yet, similar existing versions of monetary integration arrangements in the region were used in this study to draw inferences. The monetary integration arrangements in the region include the Common Monetary Area, a fixed exchange rate regime adopted by South Africa, Namibia, Lesotho and Eswatini, as well as Zimbabwe’s multicurrency regime that includes the South African Rand and the Botswana Pula. The results are largely in line with theoretical expectations except for the currency union dummy variable coefficient which was found to not be statistically significantly different from zero. This therefore means that in the case of SADC, a currency union might not have an effect on bilateral trade flows between member countries. One major limitation lies in the fact that my analysis relies on data based on currency union proxies since a SADC currency union does not already exist. Thus, any extrapolation from my results to infer the impact of an actual currency union on trade might lead to less than robust conclusions.